2016
DOI: 10.1080/02763869.2016.1152141
|View full text |Cite
|
Sign up to set email alerts
|

A Profession Without Limits: The Changing Role of Reference Librarians

Abstract: Reference librarians, specifically those working in academic health sciences environments, have expanded their roles and taken on new and unique responsibilities. While librarians at The George Washington University's Himmelfarb Health Sciences Library continue to provide traditional reference services, they have gone beyond their comfort zone in many cases to become involved in activities that are outside of the librarian's established role. This article describes the current roles of Himmelfarb's reference l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Clinical medical librarians should be open to new opportunities in their organizations and the roles in which they serve should be visible. They must perceive themselves as connectors in the health world to bridge the gap between medical literature and patient care [ 17 ]. Working on clinical care teams, they support patient care and attend rounds to gather information that both doctors and patients need.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical medical librarians should be open to new opportunities in their organizations and the roles in which they serve should be visible. They must perceive themselves as connectors in the health world to bridge the gap between medical literature and patient care [ 17 ]. Working on clinical care teams, they support patient care and attend rounds to gather information that both doctors and patients need.…”
Section: Resultsmentioning
confidence: 99%
“…The research identified in this review has found disaster management to be a collaborative role in which organizations rely on librarians’ specific skills and training as a point of contact during and before an emergency. This expectation has led to HIP involvement in various contexts: assuming additional roles on emergency management teams, designing emergency management plans, and serving as a point person with connections to all other departments [ 17 , 50 52 ]. Indeed, since librarians often serve as organizers and collaborators in multiple departments in hospitals, it follows logically that they would be primary contacts in the event of a disaster [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Librarian REB engagement roles vary, but often involve health sciences librarians rather than those in non-health areas. At George Washington University's Himmelfarb Health Sciences Library, Sullo (2016) identified serving as an IRB member as one of the institution-level roles librarians may consider. Similarly, Stemmer Frumento and Keating ( 2007) reported that the Greenwich Hospital IRB included the library director, who "conduct[s] a literature search to obtain review articles" (p. 118) for committee members.…”
Section: Overview Of Librarian Roles On Rebs/irbsmentioning
confidence: 99%
“…For example, George Washington University's health science reference librarians reported on their new roles in curriculum development, publishing support, technology support, admissions and compliance, and consulting in African countries. 59 Auckland's report sees potential roles for involvement in systematic reviews, knowledge of datasets, metadata creation, virtual networking advisory, data mining, involvement in measuring effect and quality of research, and data preservation. 60 Providing new and innovative support for faculty and student research still involves the concept of connection, the traditional role of reference librarians.…”
Section: Engaged Liaisons and Evolving Workmentioning
confidence: 99%